Ritual of cutting mango branches with a sickle - Mumbai Archive Project Team (Jio Institute, 2024)
The bride sits on the lap of her mama (maternal uncle), and together they cut the mango branches, with a sickle, signifying the abundance and wealth bestowed upon the bride’s new household.